2017
DOI: 10.1016/s2468-2667(17)30118-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multiple adverse childhood experiences on health: a systematic review and meta-analysis

Abstract: Public Health Wales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

167
2,745
21
54

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,212 publications
(2,987 citation statements)
references
References 60 publications
167
2,745
21
54
Order By: Relevance
“…Previous research has also documented the connection between adverse childhood experiences and substance use and suicide ( 6 ), underscoring the importance of preventing adverse childhood experiences as a strategy for addressing the opioid overdose crisis, reducing the prevalence of suicide, and preventing leading causes of death in the United States. Prevention of adverse childhood experiences is possible with state and community efforts to build resilient families and communities, provide parental support to develop positive parenting and coping skills, and increase access to, and use of, comprehensive health services ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has also documented the connection between adverse childhood experiences and substance use and suicide ( 6 ), underscoring the importance of preventing adverse childhood experiences as a strategy for addressing the opioid overdose crisis, reducing the prevalence of suicide, and preventing leading causes of death in the United States. Prevention of adverse childhood experiences is possible with state and community efforts to build resilient families and communities, provide parental support to develop positive parenting and coping skills, and increase access to, and use of, comprehensive health services ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adverse childhood experiences are common and have important implications for health and well-being ( 6 , 9 ). Whereas everyone is at risk for adverse childhood experiences, numerous studies have documented inequities in such experiences attributed to the historical, social, and economic environments in which some families live ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United Kingdom the government definition of domestic violence and abuse is: ‘any incident or pattern of incidents of controlling, coercive, threatening behavior, violence or abuse between those aged 16 or over who are, or have been, intimate partners or family members regardless of gender or sexuality. The abuse can encompass, but is not limited to: psychological, physical, sexual, financial, emotional’ (Home Office, 2018). Although this definition applies to those aged 16 or over, children also experience the harmful effects of domestic violence, as will be examined further below.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the original ACE study have been replicated many times, and a recent meta-analysis showed that individuals with four or more ACEs were at increased risk of each one of the 23 adverse health outcomes identified (Hughes et al, 2017).…”
Section: Can Aces Help Us Understand These Effects?mentioning
confidence: 93%